CRITICAL ANALYSIS OF MEDICATION MANAGEMENT PRACTICES IN ASSESSING ADHERENCE TO BEST PRACTICES AND PATIENT SAFETY PROTOCOLS IN PHARMACY SETTINGS THROUGH COMPREHENSIVE REVIEW - 1. Mohammed Hussain Ail Alyami | 2. Norah Mohammed I Teiran | 3.Ahad Mohammed J Alanazi | 4.Tahani Mubarak Muateq Alazmi | 5. Nasser Tayeb A Al Tawil | ,; 6. Saleh Nasser M Al Tawil | 7. Misfer Hadi M ALSalom | 8. Mana Saleh M Al swaid | 9. ‏Majdi Mohammed I Khawaji | ,; 10. Ali Abdulrhman Abdu Sofyani | 11. Hisham Saleh Zaidan | 12. Ahmad Abdullah M Refaei | 13. Mahdi Ahmid Ali Majrshi | 14. Ibrahim Hamad A Al Mansour |, (Chelonian Research Foundation, 2022)
This article, as a whole, casts a critical light on the pharmacy workflow through a focus on Compliance with the best practices and safety protocols of patients. A thorough evaluation of present-day medication practices and a retrospective look at their adherence to prevalent best practices and patient safety protocols is carried out. We propose recommendations for improvements based on the current state of this analysis. It underscores the significance of adhering to the best operations and safety precautions to improve patients' outcomes and limit drug-related integrity errors. KEYWORDS: Medication management, pharmacy practice, best practices, patient safety, adherence.